THE ROLE OF DIGITAL TECHNOLOGIES IN THE TOURISM SECTOR (International Conference on Economics, Finance, Banking and Management, 2025)
This article analyzes the significance of digital technologies in the tourism sector, their role in improving service quality, their adaptability to customer needs, the importance of CRM systems (Fidelio and Amadeus) in hotel management, and the insights of international experts in the field.